Patient–dermatologist agreement in psoriasis severity, symptoms and satisfaction: results from a real‐world multinational survey. (13th July 2018) - Griffiths, C.E.M.; Augustin, M.; Naldi, L.; Romiti, R.; Guevara‐Sangines, E.; Howe, T.; Pietri, G.; Gilloteau, I.; Richardson, C.; Tian, H.; Jo, S.J.
Abstract: Background: Psoriasis is a chronic immune‐mediated inflammatory disease, which often requires lifelong treatment. A strong partnership between the patient and healthcare practitioners should help to achieve effective treatment outcomes. Objective: To assess concordance of views between patients with psoriasis and their treating dermatologists relative to psoriasis severity, presence of symptoms and satisfaction with disease control achieved. Methods: We used data from the Growth from Knowledge (GfK) Disease Atlas real‐world evidence program, a syndicated, retrospective, cross‐sectional survey among dermatologists and their systemic therapy eligible patients with psoriasis, conducted across nine countries. Concordance was measured through patients and their dermatologist's identical answers to the same survey questions. Concordance was evaluated using percentage agreement between dermatologists and their patients, and Cohen's kappa (κ) statistic. The level of concordance was defined as 'none' (κ ≤ 0), 'none to slight' (0.01–0.20), 'fair' (0.21–0.40), 'moderate' (0.41–0.60), 'substantial' (0.61–0.80) and 'almost perfect' (>0.8). The analysis was conducted for the overall population and for each participating country. Results: Overall, 524 dermatologists and 3821 patients with psoriasis were included in the survey. Concordance of patient and dermatologist perceptions of psoriasis severity was fair both at diagnosis, and at the time of the survey (61% agreement, κ = 0.326 and 55% agreement, κ = 0.370, respectively). Higher levels of concordance were reported when patients assessed their psoriasis as moderate‐to‐severe (using Investigator's Global Assessment/Physician's Global Assessment [IGA/PGA] 5‐point scale of 3 or 4). Concordance regarding symptoms ranged from fair to moderate (κ = 0.241–0.575). Satisfaction with psoriasis control was fair (39% agreement, κ = 0.213). Results showed different patterns of concordance across the participating countries although a low concordance was observed on the satisfaction with psoriasis control in all of them. Conclusion: Results from this multinational real‐world survey indicate different perceptions between patients with psoriasis and their dermatologist with respect to psoriasis severity, symptoms and disease control. Abstract : Linked article: This article is commented on by P.V. Chernyshov, pp. 1404–1405 in this issue. To view this article visithttps://doi.org/10.1111/jdv.15188